Lifestyles That Impact The Choice To Visit A Café In The Northern Area Of Bandung City At West Java Province - Priansa, Donni Juni; Hanifa, Fanni Husnul (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
The trend of the growth of café in the North Bandung City Area is increasing, along with increasing mobility and the need for people to enjoy coffee in beautiful nature. The growth of the café is also in line with the growth of nature-based tourist destinations, which are increasingly attractive to visit. This study analyses how lifestyle influences the decision to visit café in North Bandung City, West Java Province. The research method used qualitative with a descriptive survey approach of 100 respondents who visited café in North Bandung City, West Java Province. Simple linear analysis is the data analysis method employed. The results showed that lifestyle positively and significantly affected the decision to visit café in North Bandung City, West Java Province. This influence is in a robust classification. Thus, the implication of this research is the need for café in the North Bandung City area of West Java Province to organize café oriented towards visitors' needs and lifestyle desires, mainly when associated with social media. This research needs to be continued by involving other aspects as variables studied, for example, social media.